Interaction between pristine nC60 and bovine serum albumin by fluorimetry: assessment of inner filter effect corrections - Zhang, Yu; Zheng, Ye; Li, Yuanjie; Liu, Shufang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionFluorescence spectrometry is widely used to investigate nanomaterial-protein interactions, a crucial component of nanomaterial safety evaluation. However, the inner filter effect (IFE) significantly distorts fluorescence data during the analysis of fullerene (nC60) -protein interactions. Systematic correction methods for this system are rarely reported.MethodsIn this study, bovine serum albumin (BSA) served as the protein model, four mathematical formulas (Lakowicz, Gauthier, Tucker, and Chen models) were comparatively evaluated for IFE correction in fluorescence analysis. The correction results were compared to propose an optimal correction method for the interaction between nC60 and BSA. Binding parameters were calculated from corrected data, and quenching mechanisms were analyzed using Stern-Volmer equations.ResultsAt room temperature with low nC60 concentrations (<2.0 × 10−5 mol/L), Chen’s model demonstrated optimal IFE correction accuracy. Corrected data indicated static quenching between nC60 and BSA, with a binding constant of K = 2.95 × 109 L/mol and approximately two binding sites.DiscussionThis study offers methodological guidance for IFE correction and accurate fluorescence analysis in the investigation of interactions between nanomaterials and biomolecules. Thus, it provides a reliable analytical method for the bio-safety assessment of nanomaterials.